Human infection by Angiostrongylus costaricensis in Venezuela: first report of a confirmed case - Incani, Renzo Nino; Caleiras, Eduardo; Martín, Milena; González, Carlos (Revista do Instituto de Medicina Tropical de São Paulo, 2007)
A proven case of human infection caused by Angiostrongylus costaricensis is reported for the first time in Venezuela. The patient was a 57-year-old female surgically operated because of signs of peritonitis with a palpable mass at the lower right quadrant of the abdomen. WBC count reported 16,600 cells/mm³, with 46% eosinophils. The tumoral aspect of ileocolic area and peritoneal lymph nodes prompted the resection of a large area of the terminal ileum, cecum, part of the ascending colon and a small part of the jejunum, where a small lesion was found. The pathology showed thickened areas of the intestinal wall with areas of hemorrhage and a perforation of the cecum. Histology showed intense eosinophil infiltration of the whole intestinal wall, granulomas with giant cells and eosinophils. Some of the granuloma surrounded round or oval eggs with content characterized by a large empty area, cells or embryo in the center, and sometimes nematode larvae. A cross section of an adult nematode worm was observed inside a branch of mesenteric artery. The intestinal affected area, the characteristics of the lesions, the presence of eggs in the submucosa with nematode larvae inside, and the observation of a nematode inside a mesenteric artery, makes sufficient criteria for the diagnosis of an infection by Angiostrongylus costaricensis.